(untitled) (International Journal of Engineering and Computer Science, 2017)
In the recent years, reversible logic has emerged as a promising technology having its applications in low power CMOS, quantum computing, nanotechnology, and optical computing. The basic gates such as AND, OR, and EXOR are not reversible. This paper presents various designs of reversible logic gates used for reversible operation & the applications as carry bypass and select adder Block. This paper also includes simulation result of forward & backward computation of reversible TSG, Fredkin & Toffoli gate. These gates are then used to design four bit Carry bypass and select Adder blocks. Methodology used for designing reversible gate is Tanner Tool Version-14.1 & technology file 0.25 micron. It is shown that the adder architecture designed using TSG Fredkin & Toffoli gate are much better & optimized as compared to existing four bit Carry bypass and select Adder in terms of low power dissipation .The four new reversible gates are also proposed in this paper.